Maqasid-Based Regulatory for Good Zakat Governance in Indonesia - Ahmad Hujaj Nurrohim; Sultan Uy Ubpon (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2026)
Indonesia’s national zakat governance continues to face institutional challenges that cannot be explained only by the gap between zakat potential and actual collection. The more fundamental issue lies in the legal design of Law No. 23 of 2011, which concentrates several functions within BAZNAS, places LAZ in a potentially subordinative position, leaves the accountability of UPZ insufficiently clear, and weakens public oversight. This article examines these institutional problems after Constitutional Court Decision No. 54/PUU-XXIII/2025 and formulates a more accountable model of zakat governance. It employs normative legal research with statutory, conceptual, and legal-policy approaches. The analysis combines regulatory governance, siyāsah māliyah, good zakat governance, and maqāṣid al-sharī‘ah. The article argues that zakat reform should not stop at administrative adjustment, but must redesign institutional functions, ensure equal accountability among operators, strengthen public reporting, integrate fiscal incentives, and develop digital accountability. It proposes a Maqāṣid-Based Regulatory Governance Model that positions the state as regulator and supervisor, while BAZNAS, LAZ, UPZ, and community-based zakat managers operate within an accountable ecosystem oriented toward mustaḥiqq welfare. Pengelolaan zakat nasional di Indonesia masih menghadapi persoalan kelembagaan berupa pemusatan fungsi, relasi BAZNAS-LAZ yang belum setara, posisi UPZ yang belum jelas, dan lemahnya akuntabilitas publik. Putusan MK No. 54/PUU-XXIII/2025 memberi momentum penting untuk membaca ulang desain UU No. 23 Tahun 2011, terutama karena pertimbangan hukumnya menegaskan perlunya pemisahan fungsi regulator, pembina, pengawas, dan operator. Artikel ini menganalisis kelemahan konstruksi hukum pengelolaan zakat nasional dan menawarkan model reformulasi tata kelola zakat yang lebih proporsional. Penelitian ini menggunakan metode hukum normatif dengan pendekatan perundang-undangan, konseptual, dan politik hukum. Kerangka analisisnya memadukan regulatory governance, siyāsah māliyah, good zakat governance, dan maqāṣid al-syarī‘ah. Temuan artikel menunjukkan bahwa reformasi zakat tidak cukup dilakukan melalui perubahan administratif, tetapi harus menyentuh pembagian fungsi kelembagaan, kesetaraan operator, akuntabilitas publik, insentif fiskal, akuntabilitas digital, dan pengukuran dampak berbasis maqāṣid. Artikel ini menawarkan Maqāṣid-Based Regulatory Governance Model sebagai model tata kelola zakat nasional yang menempatkan negara sebagai regulator dan pengawas, sementara BAZNAS, LAZ, UPZ, dan pengelola masyarakat bekerja dalam ekosistem akuntabilitas yang setara dan berorientasi pada kemaslahatan mustaḥiqq.